USAHA PENCEGAHAN PENYAKIT DAN KELAINAN GIGI DAN MULUT ANAK DENGAN MENGATUR POLA MAKAN ANAK SEJAK DINI - Sri Hartini Soemartono (Faculty of Dentistry, Universitas Indonesia, 2015)
Sufficient nutrition is needed to support growth and development including oral development in children. It comes from any food, which the consume since early of their life. The attention should be made not only the nutrition itself, but what kind of food, how, and when it was consumed, would be very affected to the oral health and development. These have carried out since the child was born, subsewuently will be adopted by the developin child as a habit. When it's not appropriate, may cause a bad habit, and responsible to be apparent of undesirable disorders.